2022
DOI: 10.3389/fnut.2022.1006127
|View full text |Cite
|
Sign up to set email alerts
|

Removing the sporoderm from the sporoderm-broken spores of Ganoderma lucidum improves the anticancer and immune-regulatory activity of the water-soluble polysaccharide

Abstract: Removing the sporoderm from the sporoderm-broken spores of Ganoderma lucidum improves the anticancer and immune-regulatory activity of the water-soluble polysaccharide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In contrast, RGLS was largely free of broken sporoderm, resulting in much better absorption. In previous studies, we found that RGLS exhibited better efficacy in immunomodulation (Li et al, 2020), antitumor (Fang et al, 2022; Shi et al, 2021; Zhong et al, 2021), antithrombotic and cardiac function improvement effects (Wang et al, 2021). This study indicated that the increased bioavailability might be one of the main reasons for the improved efficacy.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, RGLS was largely free of broken sporoderm, resulting in much better absorption. In previous studies, we found that RGLS exhibited better efficacy in immunomodulation (Li et al, 2020), antitumor (Fang et al, 2022; Shi et al, 2021; Zhong et al, 2021), antithrombotic and cardiac function improvement effects (Wang et al, 2021). This study indicated that the increased bioavailability might be one of the main reasons for the improved efficacy.…”
Section: Resultsmentioning
confidence: 94%
“…More recently, a new sporoderm-removing technology has been developed, which filters and removes the sporoderm and leads to the creation of so-called sporoderm-removed GLS (RGLS) (Li et al, 2020;Lin & Yang, 2019). Previous studies show that RGLS contains much higher contents of active components compared with BGLS (Li et al, 2020;Shi et al, 2021) and also exhibits better pharmacological activities in terms of immunomodulation and antitumor effect (Fang et al, 2022;Li et al, 2020;Shi et al, 2021;Zhong et al, 2021). However, it remains unclear whether the removal of sporoderm improves the absorption and bioavailability of active components in GLS.…”
mentioning
confidence: 99%
“…Prior research has indicated that SBSGL can suppress angiogenesis and cellular autophagy, making it a promising candidate for halting osteosarcoma progression 22 . Its immunomodulatory functions, particularly its influence on intestinal flora, have been well‐documented 21 . In addition, SBSGL can potentially reduce oxidative stress and prevent cadmium (II)‐induced hepatotoxicity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, following cell wall lysis, the resulting sporoderm-broken spores of G. lucidum (SBSGL) exhibit improved suitability for gastrointestinal absorption, with triterpenoids and polysaccharides being the predominant components. 21 While research has highlighted the anti-tumour effects of polysaccharides extracted from SBSGL and their role in inhibiting malignant tumour progression in conditions like gastric cancer and osteosarcoma, limited investigation has been conducted on the impact of SBSGL on HB. 22,23 In light of our hypothesis linking RACK1 O-GlcNAcylation to HB progression, we conducted in vitro and in vivo assessments of the effect of SBSGL on HB cells.…”
mentioning
confidence: 99%
“…In some inflammatory diseases caused by disorders of the immune system, GLP treatment is reported to inhibit the expression of caspase-3, caspase-9, IL-6, IL-1β and TNF-α and reduces the inflammatory polarization of macrophages [ 39 , 40 , 41 , 42 ]. For example, GLP is more potent in inhibiting the level of serum inflammatory cytokines in nude mice, activation of macrophage RAW264.7 and the expression of the inflammatory mediators IL-1β, TNF-α, inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 in vitro [ 43 ]. The activity of MMP-9 could also be inhibited by GLPP in a dose-dependent manner [ 44 ].…”
Section: Inhibition Of Glp On Synovial Joint Inflammationmentioning
confidence: 99%